CESMM4 : carbon & price book 2013 (ICE Publishing, 2013)
The Civil Engineering Standard Method of Measurement is used as the standard for the preparation of bills of quantities in civil engineering work. This new edition brings the method into line with changes in industry practices and extends into new areas.